2012
DOI: 10.1186/1471-2318-12-43
|View full text |Cite
|
Sign up to set email alerts
|

Limited referral to nephrologists from a tertiary geriatric outpatient clinic despite a high prevalence of chronic kidney disease and anaemia

Abstract: BackgroundChronic kidney disease (CKD) is increasing in prevalence world-wide with the largest growth being in the elderly. The aim of this study was to examine the prevalence of CKD in a geriatric outpatient clinic within a tertiary hospital and its association with anaemia and mortality with a focus on the referral patterns towards nephrologists.MethodsRetrospective study utilising administrative databases. The cohort was defined as all patients that attended the geriatric outpatient clinics of a single tert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…26 Furthermore, among over 400 geriatric ambulatory patients with mild to moderate CKD, only 8.8 % were referred to a nephrologist. 27 In contrast, in a study of 135 patients initiating dialysis, no association was found between age, gender or race and timing of nephrology referral, but private health insurance conferred a higher odds of nephrology referral compared with Medicare. Factors that might influence primary care providers' (PCP) referral of patients with CKD to nephrologists are not well understood.…”
Section: Discussionmentioning
confidence: 94%
“…26 Furthermore, among over 400 geriatric ambulatory patients with mild to moderate CKD, only 8.8 % were referred to a nephrologist. 27 In contrast, in a study of 135 patients initiating dialysis, no association was found between age, gender or race and timing of nephrology referral, but private health insurance conferred a higher odds of nephrology referral compared with Medicare. Factors that might influence primary care providers' (PCP) referral of patients with CKD to nephrologists are not well understood.…”
Section: Discussionmentioning
confidence: 94%
“…The fact that 10,5% of geriatricians asked for nephrological consultation only for stage 5 CKD patients and 30,9% only for stage 4 or 5 confirms findings pertaining to a tertiary geriatric outpatient clinic [ 16 ]. Paradoxically, comorbidity, i. e. an index of complexity of the health status, has been reported to characterize patients for whom general practitioners did not ask for nephrologic consultation [ 17 ].…”
Section: Discussionmentioning
confidence: 53%